NATIONALISM AS A FACTOR OF SOCIAL AND POLITICAL TRANSFORMATIONS - A. Bakanach (Вестник университета, 2016)
This article focuses on the nationalism in Russia towards post-Soviet republics. Discusses the concept of nationalism, identified three main approaches to the problem of nationalism. An example of the nationalism in Russia on the basis of sociological analyses. Today this issue is topical in the light of the recent events in Ukraine, emerging nationalism in Belarus and the CIS countries.